Lipoma of the parotid gland - Christopher, Yeoh; Min Han, Kong; Azman, Mawaddah; Ahmad Affandi, Khairunisa; Tan, Geok Chin (Egyptian Society of Ear Nose Throat and Allied Sciences, 2019)
Introduction: Lipoma of the parotid gland is rare in the head and neck region. It is a soft tissue benign tumor originating from areas composed of fat. Occurrence of lipoma is often sporadic and rarely inherited. Case report: A 74-year-old male presented with a left sided neck swelling which was gradually increasing in size over a duration of 10 years. It was associated with intermittent pain 6 months prior to presentation. Discussion: Lipoma is the commonest benign mesenchymal tumor and is a relatively uncommon presentation in the head and neck region. Often a fine needle aspiration cytology is able to indicate the presence of a lipoma. However, with the computed tomographic scan, the level of attenuation is able to indicate the presence of a lipoma. Although benign, there are reports of malignant transformation to a liposarcoma. Conclusion: Lipoma of the parotid gland is often mistaken for other tumors hence an accurate clinical assessment together with preoperative imaging and histopathological examination helps to facilitate the diagnosis.